2022
DOI: 10.3390/molecules27020444
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Orthosiphon stamineus Benth. in the Treatment of Diabetes and Its Complications

Abstract: (1) Background: Orthosiphon stamineus Benth. is a traditional medicine used in the treatment of diabetes and chronic renal failure in southern China, Malaysia, and Thailand. Diabetes is a chronic metabolic disease and the number of diabetic patients in the world is increasing. This review aimed to systematically review the effects of O. stamineus in the treatment of diabetes and its complications and the pharmacodynamic material basis. (2) Methods: This systematic review was conducted following Preferred Repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 138 publications
(179 reference statements)
1
10
0
Order By: Relevance
“…On the other hand, the high dose of O. aristatus was able to reduce the HOMA-IR value to 1.70 ± 0.463, indicating a significant reverse in the insulin resistance condition. This result is in line with several previous studies that have proposed O. aristatus as an alternative treatment for type 2 diabetes [ 11 , 29 , 37 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, the high dose of O. aristatus was able to reduce the HOMA-IR value to 1.70 ± 0.463, indicating a significant reverse in the insulin resistance condition. This result is in line with several previous studies that have proposed O. aristatus as an alternative treatment for type 2 diabetes [ 11 , 29 , 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…This broad spectrum of benefits is attributed to the rich phenolic content, including polyphenols, diterpenes, triterpenes, lipophilic flavones, glycosides and caffeic acid derivatives such as rosmarinic acid (RA) [ 9 , 10 ]. O. aristatus is reported to have α-amylase and β-glucosidase inhibitory activities, exhibits antioxidant and anti-inflammatory properties, regulates lipid metabolism, promotes insulin secretion, improves insulin resistance, increases glucose uptake, promotes glycolysis and inhibits gluconeogenesis [ 11 ]. More importantly, a previous study provides evidence for the anti-obesity effect of O. aristatus through the inhibition of pancreatic lipase [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 2,3-Dihydro-3,5-dihydroxy-6-methyl-4H-pyran-4-one (7.12%) is also found as one of the major compositions, reported for effective inhibition of colon cancer cell growth (Ban et al 2007 ) and antioxidant activity (Chen et al 2021 ). In addition, vanillic acid (4-hydroxy-3-methoxy benzoic acid) is a phenolic derivative from plants known to possess anti-filarial, antibacterial, antioxidant, and anti-diabetic (Vinothiya and Ashokkumar 2017 ; Wang et al 2022 ), etc. Previous studies demonstrated maltol’s effectiveness against oxidative damage (Song et al 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Orthosiphon stamineus Benth. (Lamiaceae) is a perennial herb found in tropical and subtropical regions [ 7 ]. O. stamineus is used in folk medicine as an antidiabetic and diuretic and for treating abdominal pain, kidney and bladder inflammation, edema, and gout [ 8 ].…”
Section: Introductionmentioning
confidence: 99%